Implications of all season Arctic sea-ice anomalies on the stratosphere - Cai, Duy Sinh; Dameris, M.; Garny, H.; Runde, T. (Atmospheric Chemistry and Physics, 2012)
Abstract. In this study the impact of a substantially reduced Arctic sea-ice cover on the lower and middle stratosphere is investigated. For this purpose two simulations with fixed boundary conditions (the so-called time-slice mode) were performed with a Chemistry-Climate Model. A reference time-slice with boundary conditions representing the year 2000 is compared to a second sensitivity simulation in which the boundary conditions are identical apart from the polar sea-ice cover, which is set to represent the years 2089–2099.